Trump studies : an intellectual guide to why citizens vote against their interests - Brabazon, Tara; Redhead, Steve; Chivaura, Runyararo S. (Emerald Publishing Limited, 2018)
Why do citizens vote against their own best interest?Trump Studies addresses this key question; probing the value of thinking, reading, writing and interpretation during times of economic, social and political uncertainty. With a compelling voice and academic rigour, the authors explore how and why xenophobia and sexism are the grammar of contemporary popular culture and politics.The Brexit result and the Trump victory cannot be studied in a laboratory; the silent majority will not sit in a petri dish, waiting to be researched. The theories and methodologies developed into this book not only explain these two mega and meta events, they create space for ideas that challenge and dissent, and make the case for the role and value of universities in a time when evidence, expertise and facts often dissolve into opinion, emotion and fake news.Donald Trump does not matter. Trump Studies does matter - and this is a siren call to all intellectuals to intervene and transform the currency of theory in empiricist times.
Includes index.
Keywords: Trump, Donald, -- 1946-; Presidents -- United States -- Election -- 2016.; Voting -- United States -- Psychological aspects.; Social Science -- Popular Culture.; Popular culture.; elektronické knihy; electronic books